Motivations driving satisfaction and loyalty in cultural festivals: the case of Bahrain’s spring of culture festival - Carvache-Franco, Mauricio (2025)
This study examines the intrinsic motivations driving tourist satisfaction and loyalty at Bahrain’s Spring of Culture Festival. Based on data from 389 valid surveys, a structural equation model using the partial least squares technique was applied to analyze causal relationships. The results identified cultural exploration, novelty, and socialization as the primary motivations influencing satisfaction. Among these, cultural exploration emerged as the most significant factor, highlighting tourists’ pursuit of enriching experiences. Novelty and socialization were also found to positively influence satisfaction by offering unique activities and opportunities for personal interaction. Satisfaction, in turn, showed a positive impact on loyalty, demonstrated in attendees’ intentions to return and share positive word-of-mouth about the festival. From a theoretical point of view, this study emphasizes the importance of integrating motivational dimensions to better understand the cultural tourism experience. From a practical perspective, it recommends culturally engaging programs, innovative technology-driven experiences, and strategically designed interaction spaces to enhance satisfaction and build loyalty, thereby contributing to the development of more sustainable cultural events.